THE ANALYTICAL CORE MODEL FORMATION OF THE NONLINEAR PROBLEM BOND ARMATURE WITH CONCRETE (Academic journal Industrial Machine Building Civil Engineering, 2017)
It is proposed a nonlinear analytical model of the pivotal bond between the reinforcementand the concrete. It is established, that at the design of this process it is important to reach thelevel of engineering visibleness of the used dependences, dropping not essential features, whileat the same time to get a reasonably accurate solution. In such search authors were stopped forthe analytical model of nonlinear task of bond armature with a concrete, allowing to take intoaccount elastic-plastic work of concrete, and also non-linearity of contact armature with aconcrete. It is revealed that analytically the rod model of bond reinforced concrete bar isdesigned by the system, consisting of four equalizations, two from which are differentialequalizations of first order. Nonlinear contact interaction of two materials is approximatelyexamined as mutual relative displacements of armature and concrete. It is shown that theproposed model undoubtedly requires experimental confirmation by testing and numeral designmore high level and degrees of working out in detail.Keywords: analytical model, bond armature with concrete, reinforced concreteconstructions, physical nonlinearity, mutual relative displacement of reinforcement and concrete.